Rooting behaviour of chickpea (Cicer arietinum) as affected by soil compaction levels in Vertisol of central India - K CHOUDHARY; M MOHANTY; NISHANT K SINHA; A RAWAT; K M HATI; RITESH SAHA; J SOMASUNDARAM; R S CHAUDHARY (The Indian Journal of Agricultural Sciences, 2015)
Soil compaction may restrict deep root growth and adversely affect plant access to sub-soil layer. Therefore it is important to study rooting behaviour of crops to soil compaction that are imparted on it naturally or artificially. The objective of this study was to determine the effect of soil compaction levels by varying the soil bulk density (BD) on rooting parameters and to model the root growth to understand the dynamics of rooting behaviour of chickpea (Cicer arietinum L.). Compaction level treatments, i.e. BDs were (i) 1.2, (ii) 1.4, (iii) 1.5 and (iv) 1.6 Mg/m3. When BD was increased from 1.2 Mg/m3 to 1.6 Mg/m3, there was 58% and 44% reduction in plant height of JG 11 and JG 130, respectively. There was 59% and 45% reduction in root length of JG 11 and JG 130, with increase in BD from 1.2 Mg/m3 to 1.6 Mg/m3. On an average, an increase in BD by 0.1 unit resulted in 19.34 and 19.11% decrease in root main axis length of JG 11 and JG 130, respectively. There was a negative correlation between root penetration rate and soil BD (R2 = 0.88). The critical growth limiting BD for chickpea was found to be 1.89 Mg/m3 in our study. The logistic growth model was fitted well with the observed dataset obtained from study with R2 of 0.98** (P < 0.01). In this study, the chickpea variety JG 130 proved to be better than JG 11 while selecting chickpea cultivars for highly compacted soils.